Concept Substantiation of Duplicate Measurement Accuracy - V. A. Anishchenko; A. S. Nemkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper presents technological concept substantiation of duplicate measurements which is based on the account of apriori information on measured variable and aposteriori information pertaining to the value of measurement imbalance. Decision-making boundaries in respect of truth have been determined in the paper and when there is bound violation it is necessary to substitute an averaged variable value with its more probable one.